Intergenerational Communication Patterns in Maintaining the Existence of Selapanan Recitation in Purworejo - Mujib; Mohamad Madum; Akhmad Muhaini (Journal of Communication Studies, 2026)
Communication as a means of transmitting values, traditions, and religious identities in society, especially in maintaining the sustainability of traditional religious activities such as selapanan recitation involving various age groups. The background of the research shows that the difference in communication characteristics between the older generation and the younger generation in the digital era has the potential to cause a communication gap that can affect the sustainability of traditions. The purpose of this study is to analyze and describe the intergenerational communication pattern that occurs between religious leaders, the older generation, and Generation Z in maintaining the existence of the Selapanan Recitation in Tepus Hamlet, Somorejo Village. The research method uses a qualitative approach with a case study method through participatory observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results of the study show that the sustainability of the selapanan recitation is influenced by the application of dialogical, participatory, and multidirectional communication patterns, where the older generation plays the role of guardians of values and traditions, while the younger generation plays the role of an agent of adaptation to social change. The conclusion of the study emphasizes that open and inclusive intergenerational communication is able to create a balance between preserving tradition and adapting to the times so that the recitation of the selapanan remains relevant as a spiritual and social space for the community.